(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Reducing maternal mortality has been a constant struggle globally. The major causes of maternal mortality remain to be ante and post-partum haemorrhage, anaemia, obstructed labour, hypertensive disorders and post-partum infections, liver disorders as observed in various studies. The present study was carried out with view to determine factors causing maternal deaths, and utility of autopsy with autopsy record as a useful and adjunct data source for ascertainment of maternal deaths. In this study we have retrospectively considered the autopsy of maternal cases during 2015 to 2019 referred to RCSM GMC Kolhapur, Kolhapur, Maharashtra. Of the total 66 cases of maternal deaths, maximum number of cases were seen in age group of 20 to 29 years comprising 42 out of 66 (63.63%), Maximum cases 53 (81.30%) were resident of rural areas. Maximum causes of death on autopsy were direct causes, of which hemorrhage was the predominant cause. Most of the cases (42 out of 66 ) died within 24 hours of admission to the hospital. The determinants of maternal mortality need to be studied through the lens of autopsy.